Contemporary crustal stress of the Greek region deduced from earthquake focal mechanisms - V. Kapetanidis; Kassaras, I. (Journal of Geodynamics, 2019)
A massive dataset of over 1900 focal mechanisms of crustal earthquakes with M ≥ 3.5 in the Greek region was employed to resolve the contemporary stress-field using a damped least-squares inversion. The results are in good agreement with the strain-rate field of the Global Strain Rate Model, which was used as reference, both in terms of their principal axes orientations and expected faulting styles. Dual stress-states were identified using the Multiple Inverse Method in regions delineated by joining neighboring Area Sources of the European Seismic Hazard Model 2013 (ESHM13). North-western Greece is mostly affected by transpressional tectonics characterized by NE-SW contraction. Northern/central Greece and the Corinth Rift are dominated by E-W normal faulting, with secondary oblique-normal to strike-slip faulting at the western margin of the latter. North and central Aegean are mainly governed by transtensional regime, characterized by stable N-S extension. The stress-tensor was found to be compatible with the Fault Sources (FS) of ESHM13, in terms of orientation and expected faulting type. Differences were observed in regions of low strain-rate, such as the Southern Aegean, where left-lateral, E-W strike-slip instead of normal faulting was inferred. Discrepancies in areas with strong local heterogeneities were highlighted by anomalies in the stress-ratio, Φ, indicating transtensional regime in the pull-apart basins of Western Greece and transpressional tectonics in north-western Greece and south of Crete. The latter is characterized by stable N-S contraction, SW-NE sinistral strike-slip and E-W reverse faulting in the vicinity of the subduction zone. A low Φ, E-W oriented zone was identified along the active volcanic arc, where a remarkable 90° rotation occurs in the stress field. This rotation is related to the transition from E-W (in the north) to N-S (in the south) normal faulting in Peloponnese and Dodecanese Islands, as well as rearrangement from dextral to sinistral SW-NE strike-slip faulting in North and South Aegean, respectively.
Keywords: Continental deformation; Focal mechanisms; Hellenic subduction; seismic hazard; Strain rate; Stress tensor